Seasonal Abundance of Mustard Aphid, Lipaphis Erysimi (Kalt.) and Saw Fly, Athalia Lugens Proxima (Klug) in Relation to Abiotic Factors and their Eco-Friendly Management - Kalita, H.; Avasthe, R. K.; Gopi, R.; Kapoor, C. (International Journal of Bio-resource and Stress Management, 2023)
Effect of weather on abundance of mustard aphid and sawfly and their eco-friendly management was studied during 2011-13. Mustard aphid, Lipaphis erysimi appeared first in 49th and 50th standard week and reached maximum in 2nd standard week (49.07 and 63.48 aphids 10 cm-1 central inflorescence during 2011-12 and 2012-13, respectively). Sawfly appeared in 45th and 46th standard week and attained maximum in 47th standard week (1.57 and 1.42 larvae plant-1 during 2011-12 and 2012-13, respectively). The correlation study revealed that minimum and maximum temperature had significant negative influence on aphid population (r=-0.64 to -0.83 during 2011-12 and 2012-13) whereas saw fly population was influenced positively by both temperature (r=0.62 to 0.67 in both the periods). Of 14 germplasm of rapeseed-mustard screened against mustard aphid and sawfly, Sikkim Toria-2, Sikkim Sarson Yellow-1, Sikkim Sarson Yellow-3 and TS-38 were found promising. Among the biopesticides evaluated against mustard aphid and sawfly, Bacillus thuringiensis @ 2 g l-1 was found to be effective for management of sawfly population (68.60 % larval reduction over control) while petroleum agro-spray @ 10 ml l-1 and neem oil 0.15EC @ 3 ml l-1 were most effective for controlling of aphid population. Among treatments the highest yield (7.8 q ha-1) was recorded in the plot treated with petroleum agro-spray followed by neem oil (7.6 q ha-1) and were on par with check oxydemeton methyl 25EC @ 1 ml l-1. Coccinella septempunctata and Menochilus sexmaculata were recorded more (0.35-0.70 nos. plant-1) with higher predatory efficiency (8.4-12.6 aphids day-1) in comparison to syrphid fly.